2005
DOI: 10.1080/00288233.2005.9513645
|View full text |Cite
|
Sign up to set email alerts
|

Tests on a new bait for flies (Diptera: Calliphoridae) causing cutaneous myiasis (flystrike) in sheep

Abstract: A synthetic bait consisting of sulphurcontaining volatile compounds encapsulated in a casein-based slow release matrix was used in sticky and non-return traps to catch sheep strike flies (Diptera: Calliphoridae) in the field. The synthetic bait caught significantly more individuals of a minor strike fly Chrysomya rufifacies than a liver/sodium sulphide mixture. The synthetic bait also caught a significantly higher proportion of gravid C. rufifacies than the liver mixture. The synthetic bait did not trap signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Entry traps, or sticky surfaces that combine olfactory and visual stimuli, commonly are used to trap blowflies (Broce et al, 1977;Jiron, 1984;Anderson et al, 1990;Green and Warnes, 1992;Wall et al, 1992;Wall and Smith, 1996;Hall et al, 2003). Synthetic lures also have been developed for screwworm flies (Mackley and Brown, 1984;Horton et al, 1999;Morris, 2005;Urech et al, 2009). In this study, we demonstrated that mass trapping of C. vicina blowflies is an economically viable control method in stockfish production.…”
Section: Discussionmentioning
confidence: 76%
“…Entry traps, or sticky surfaces that combine olfactory and visual stimuli, commonly are used to trap blowflies (Broce et al, 1977;Jiron, 1984;Anderson et al, 1990;Green and Warnes, 1992;Wall et al, 1992;Wall and Smith, 1996;Hall et al, 2003). Synthetic lures also have been developed for screwworm flies (Mackley and Brown, 1984;Horton et al, 1999;Morris, 2005;Urech et al, 2009). In this study, we demonstrated that mass trapping of C. vicina blowflies is an economically viable control method in stockfish production.…”
Section: Discussionmentioning
confidence: 76%
“…Both species were present, but C. megacephala was the major damagecausing species (Esser 1991). Oligosulphides are only a minor component of the lures developed for blowfly parasites (Mackley and Brown 1984;Morris 2005;Urech et al 2009), indicating differences in the use of chemical cues between the specialists and generalists reported to attack fish (Esser 1991;Sømme and Gjessing 1963;Wall et al 2001). These differences emphasize the need for target-specific lures and if dimethyl trisulphide is a common attractant for primary saphrophagous blowflies, such as Calliphora spp., its use might be transferrable to other areas of the world where control of blowflies is needed to prevent food damage.…”
Section: Discussionmentioning
confidence: 94%
“…Synthetic blowfly lures are available for trapping of screwworms and other sheep-striking blowflies (Mackley and Brown 1984;Morris 2005;Urech et al 2009). No such bait is commercially available for the genus Calliphora, but there are reports of attraction to oligosulphides (Nilssen et al 1996;Stensmyr et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…In the case of blow flies, volatile organic compounds released by bacteria are the primary mechanism governing their attraction, acceptance and colonization of such resources (Eisemann and Rice, 1987;Chaudhury et al, 2002Chaudhury et al, , 2010Morris, 2005). However, no one has demonstrated the role of these volatile compounds in the ecology of the bacteria from which they are released.…”
Section: Discussionmentioning
confidence: 99%